Relationship between hepatitis B virus reverse transcriptase 181 mutation and S gene mutation in hepatitis B virus chronically infected patients - Wang, L-P.; Han, F-Z.; Yan, X-B.; Fan, Y-C.; Wang, K. (Cellular and Molecular Biology, 2016)
This study aims to explore clinical significance of HBV rt181 mutation. Serum samples were collected from 226 CHB patients with no anti-viral treatment, and 72 patients with adefovir dipivoxil treatment over 1 year. HBV genes of reverse transcriptase regions were amplified by nested PCR. HBV DNA in pre-S/S regions sequences were determined by sequencing. Mutations in HBV were characterized by mutational analysis. Results indicated that resistant mutation was found in 16 samples (7.08%) with no anti-viral treatment. It showed higher prevalence in patients with adefovir dipivoxil treated samples 30/72(41.67%). Mutation sites of pre-existing and adefovir dipivoxil induced resistance were different (adefovir dipivoxil induced resistance mode is rtA181T/V, and pre-existing mode is the other). Resistance mutation was found just in genotype C patients. Among 25 containing rtA181T/V mutation patients, 7 rtA181T mutation cases with sW172L, 6 rtA181T mutation cases with sW172*, 12 rtA181Vmutation cases with sL173F. In conclusion, mutation sites of pre-existing and adefovir dipivoxil induced resistance were different. HBV genotype C is prone to occur resistance mutation than genotype B. rtA181T mutation was accompanied with not only sW172 * mutation, but also sW172L mutation, rtA181V mutation was accompanied with sL173F mutation or Pre-S2 initiation codon to termination mutation.